Intermestic Learning in Indonesian Decentralization Policy Change: A Capillarity Process - Dyah Estu Kurniawati (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study aims to understand the process of Indonesian decentralization policy change in 1999 as an interplay of international and domestic (intermestic) ideas and actors. It shows the importance of discourse role in the policy change process that across political domain. Eventually, domestic and international dichotomy in the process of policy change are not applicable due to the thatched ideas and actors who bring a certain discourse and influence the learning process. Because of the learning process wasinvolving international and domestic actors, the process of learning in policy change is referred to as intermestic learning.